Host phenotype and microbiome vary with infection status, parasite genotype, and parasite microbiome composition. Issue 5 (27th January 2022) - Hahn, Megan A.; Piecyk, Agnes; Jorge, Fátima; Cerrato, Robert; Kalbe, Martin; Dheilly, Nolwenn M.
Abstract: A growing literature demonstrates the impact of helminths on their host gut microbiome. We investigated whether the stickleback host microbiome depends on ecoevolutionary variables by testing the impact of exposure to the cestode parasite Schistocephalus solidus with respect to infection success, host genotype, parasite genotype, and parasite microbiome composition. We observed constitutive differences in the microbiome of sticklebacks of different origin, and those differences increased when sticklebacks exposed to the parasite resisted infection. In contrast, the microbiome of successfully infected sticklebacks varied with parasite genotype. More specifically, we revealed that the association between microbiome and immune gene expression increased in infected individuals and varied with parasite genotype. In addition, we showed that S . solidus hosts a complex endomicrobiome and that bacterial abundance in the parasite correlates with expression of host immune genes. Within this comprehensive analysis we demonstrated that (i) parasites contribute to modulating the host microbiome through both successful and unsuccessful infection, (ii) when infection is successful, the host microbiome varies with parasite genotype due to genotype‐dependent variation in parasite immunomodulation, and (iii) the parasite‐associated microbiome is distinct from its host and impacts the host immune response to infection.